Trade Ethics in the Qur'an According to Tafsir al-Munir by Wahbah Az-Zuhaili - Nida Rofana Faridah; Akhmad Sulthoni; Indri Astuti (CV. Doki Course and Training, 2025)
Islam is a source of values and ethics that provide guidance for its adherents, including in the discourse of trade. This research focuses on analyzing the ethics of trade in the verses of the Qur'an by referring to the interpretation of Wahbah Az-Zuhaili in Tafsir al-Munir. The purpose of this study is to find out how the ethics of trade in the Qur'an, so that Muslims are expected to carry out trade in a way that supports welfare and avoids unethical practices in the world of trade. The research method used is qualitative with the type of literature. While the data analysis technique used is descriptive-analytical with thematic interpretation method. The results show that trade in the Qur'an has two meanings, namely human trade with God and human trade with humans. There are five basic principles in trading with fellow humans, namely the principles of unity, balance, free will, responsibility, truth (virtue and honesty). In az-Zuhaili's interpretation, he relates to the laws of muamalah fiqh where one must have guidelines for behavior in trade affairs in Islam, namely morals and ethics, validity of transactions, justice and equality, prohibition of usury, ownership and management of property, transparency and disclosure, and contracts and agreements. This article contributes in a practical way to the daily life of commerce, especially in relation to trade where Muslims are required to comply with the guidelines set out in the Qur'an.